Polarization State of Macrophages Under Lactate Action - Li, Sixuan (Transactions on Materials, Biotechnology and Life Sciences, 2024)
As the most prevalent immunological population in the tumor microenvironment (TME), tumor associated macrophages (TAMs) are crucial to TME. Simultaneously, acidic environment is a prominent feature in TME. Recent studies have shown that macrophages undergo further division into two distinct types of TAMs, namely M1 and M2, respectively. They are induced by different inducing factors and play different roles in cancer and inflammation. Lactic acid strongly enhances the transformation of macrophages with M1 designation into macrophages with the M2 designation, as shown by the increased expression of M2 genes. This article analyzes EC lactate and obtains the results of its transportation in the form of MCT1 lactate transporter. There is also an epigenetic mechanism that promotes macrophage polarization. Using lactate as a target, MCT1 inhibitor AZD3965 can inhibit the expression of M2 macrophages. Because it only discusses lactic acid in acidic environments, it has limitations. This article provides reference for future research on lactate, and the specific mechanism of action of HIF-1 α in lactate environment has not been resolved. Future research can focus on this direction.